Who regulates? Effects of scaffolding in system- and self-regulated learning - Herold, Aileen; Seufert, Tina (Frontiers in Psychology, 2025)
BackgroundIn adaptive learning settings, fine-grained dynamic measurements of learner characteristics (e.g., prior knowledge) and system-based decisions (e.g., adjusting task difficulty) enable learners to follow an individual learning path. Thus, the system takes over the regulation of the learning process. According to self-regulated learning, the learners could also do this themselves. Scaffolding offers a possibility to support the learner in system-based settings and self-regulated learning situations by making system decisions comprehensible and compensating for problems in self-regulation.ObjectivesThis study aims to investigate the influence of the agency of regulation (self-regulation/system-regulation) in combination with scaffolding (with/without) on learning performance and self-efficacy.MethodsWe conducted a 2 × 2 experimental study with N = 102 participants (students in psychology and teacher education), studying in a digital learning environment. The effect of agency of regulation was examined as an open research question. We hypothesized that learning performance and self-efficacy are higher in the groups with scaffolding. Metacognitive competencies and prior knowledge are analyzed as moderators. Data analysis was conducted using ANCOVAs and moderation analyses.ResultsThe results showed a significant main effect of scaffolding on learning performance (recall) and self-efficacy. Furthermore, the results revealed a significant moderation effect regarding prior knowledge. An interaction effect and a main effect for the agency of regulation were not found.ConclusionIn further studies, the role of scaffolding within the interplay of system-based learning and self-regulation should be investigated in more depth by including the design of scaffolds and individual self-regulatory processes.